SUCCESSFUL PERVAGINAL DELIVERY OF A SEVERE HYDROPERITONEAL FETUS IN A BUFFALO - BISWAL, S S; DAS, A K; BALASUBRAMANIAN, S; SARATH, T; RANGASAMY, S; SABARINATHAN, A (The Indian Journal of Animal Reproduction, 2023)
A graded buffalo at fourth calving was presented with the history of persistent straining and unableto deliver the fetus. Clinical examination revealed dystocia due to posterior presentation with severe fetalhydroperitoneum. Successful pervaginal delivery was carried out by obstetrical mutation, abdominocentesisand controlled traction. Post mortem examination with histopathological study revealed hydronephrosis withtubular degeneration.
Keywords: Hydroperitoneum; Posterior Presentation; Dystocia; Buffalo; Hydronephrosis